KEPEMIMPINAN DAN BUDAYA ORGANISASI DI PESANTREN - Hosaini, Ahmad (Jurnal Likhitaprajna, 2015)
The aim of this article is to explore the concept of leadership and organizational culture on Islamic Boarding School. This article would also discuss about the relationship between leadership and organizational culture in Islamic Boarding School and also how the impact of them can develop commitment and satisfaction of personnel in that organization. In order to know about several beneficial performance of organization, this article aim of influence leadership and organizational culture in Islamic Boarding School on performance of organization. This article will be concluded with an argument that gaining deeper insight on the theoretical base of leadership in relation to organizational culture can be a valuable paradigm for the organization. The design used in this study is qualitative research with library research. The data collections are gathered from three steps, are: (1) orientation; (2) exploration; and (3) study focused. The result of this study shows that despite the relation between leadership and organizational culture, however gaining deeper theoretical insight into leadership is still an important objective, especially to be related to the performance of organization.Â  Keywords: leadership, organizational culture, islamic boarding school